GREY PREDICTION FOR THE REMAINING LIFE OF CORROSION NOZZLE OF SEPARATOR - YU ShuRong; LUO WenQiang (Jixie qiangdu)
In view of the problem that the triphase separator of offshore platform is confronted with serious partial corrosion which has less corrosion data and more corrosion factors. Grey prediction model is established for residual thickness of nozzle,at the entrance of separator,taking the phenomenon of the thickness with the corrosion reduction as grey global parameters. In view of the data are not pre-processed and the new information is not fully utilized in traditional GM（ 1,1）,moving the data and using the latest accumulated value as the setting condition to improve the original prediction model. Analyzing the problems happened in the process of improvement at the same time. The effectiveness of the improvement is proved by comparison with the accuracy of other three grey forecasting models. On this basis,the remaining life of the nozzle is calculated which could provide a reference for the management to develop the corresponding corrosion prevention plan.